The Effect of Work Experience, Work Discipline, and Physical Health on Employee Productivity at the KPP Madya Surabaya - Ramdhan, Moch. Sonyviel; Purwanto, Purwanto; Rahayu, Sri (International Publisher (YAPENBI), 2026)
Employee productivity is a crucial factor in determining organizational performance in the public sector, particularly within tax administration institutions characterized by high workload intensity, strict accuracy requirements, and performance targets. This study aims to analyze the effect of work experience, work discipline, and physical health on employee productivity at KPP Madya Surabaya. A quantitative approach with a causal associative design was employed. Data were collected through structured questionnaires distributed to 124 employees using a census method and analyzed using multiple linear regression with SPSS. The results indicate that work experience, work discipline, and physical health each have a positive and significant effect on employee productivity. Among the three variables, work experience emerges as the most dominant determinant, followed closely by physical health, while work discipline also contributes significantly. Simultaneously, the regression model demonstrates strong explanatory power, indicating that these individual human capital factors jointly explain a substantial proportion of employee productivity in the studied institution. These findings suggest that employee productivity in tax administration institutions is strongly influenced by individual human capital attributes rather than organizational procedures alone. By integrating work experience, discipline, and physical health within a single empirical model, this study extends the public sector human resource management literature and provides practical insights for policymakers and managers in designing experience-based development programs, reinforcing disciplinary systems, and supporting employee health to enhance productivity.